Students Ability and Problem in Pronouncing English Vowels Made By the Second Semester Students of Universitas Negeri Padang - Muhammad Zaki Arevi; Ratmanida Ratmanida (Journal of English Language Teaching, 2020)
This study aimed to find out students’ ability and problem at English Education of Universitas Negeri Padang. This research is designed as descriptive qualitative research. In this study, the researcher focused on the first year students of English Education program in Universitas Negeri Padang in the Academic Year of 2019/2020. There are 20 students as the subject of the research. The process of data collection in this research had to be put in two activities, those are: recording and transcription. The findings of this research indicate that most vowels are pronounced well by the students. There are nine vowels classified as excellent category, they are vowels are vowel /e/ 79,5 (99.4%), vowel /i:/ 78,5 (98.12%), vowel /I/ 78 (97.5%), vowel /ɑ:/ 77,5 (96.9%), vowel /ə/ 76 (95%), vowel /u:/ 75,5 (96.9%), vowel /ɔ:/ 72 (90%), vowel /ɛ:/ 67,5 (84.34%), and vowel /ɑ/ 65 (81.25%). And there are three vowels classified as good category which vowels are vowel /ʌ/ 62 (77.5%), vowel /æ/ 56 (70%), and vowel /ʊ/ 55,5 (69.4%).